Implementing Merdeka Belajar Curriculum: Strategies for Early Childhood Students at Yogatama Playgroup - Esti Stiasih; Edi Harapan; Muhammad Fahmi (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2024)
There are still doubts about teachers implementing the Merdeka Belajar curriculum; several of the reasons include: (1) Teachers have not fully understood the Merdeka curriculum; (2) The spirit of curiosity of teachers about the Merdeka curriculum is still low so that training on the Merdeka curriculum through online are often ignored; and (3) Face-to-face training expected by teachers is still very minimal; (4) The assumption that the implementation of the Merdeka curriculum must be with complete facilities. However, the main problem is the low ability of teachers to master information technology. Of the six (6) personnel, both teachers and heads of PAUD institutions of the Yogatama Play Group, only two (2) people can operate laptops and access information through online media. The results of the study show that the strategy of implementing the Merdeka Belajar curriculum for PAUD students of the Yogatama Play Group has been well prepared and is by the expectations of all parties, even though in the application of the principles of the new Merdeka Belajar curriculum at the initial stage, namely the Merdeka Belajar stage whose learning tools still use the 13 curriculum or the emergency curriculum.